2001
DOI: 10.1093/brain/124.2.361
|View full text |Cite
|
Sign up to set email alerts
|

A study of the cortical processing of ano-rectal sensation using functional MRI

Abstract: Investigation of human ano-rectal physiology has concentrated largely on understanding the motor control of defecation and continence mechanisms. However, little is known of the physiology of ano-rectal sensation. There are important differences in the afferent innervation and sensory perception between the rectum and anal canal. This suggests that there could also be differences in the brain's processing of sensation from these two areas; however, this possibility remains unexplored. The aim of our study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 36 publications
6
99
0
4
Order By: Relevance
“…[61][62][63][64] Furthermore, some studies reported activations in ACC during non-painful visceral distension implicating the role of this region in the control of autonomic visceral responses rather than to pain perception. 18,27,65,66 However, we observed the activations only during painful visceral distension, which might be another reason for the absence of activations in ACC. Activations in the amygdala and hippocampus in female IBS patients during rectal distension suggests an exaggerated emotional arousal network.…”
Section: Discussionmentioning
confidence: 55%
“…[61][62][63][64] Furthermore, some studies reported activations in ACC during non-painful visceral distension implicating the role of this region in the control of autonomic visceral responses rather than to pain perception. 18,27,65,66 However, we observed the activations only during painful visceral distension, which might be another reason for the absence of activations in ACC. Activations in the amygdala and hippocampus in female IBS patients during rectal distension suggests an exaggerated emotional arousal network.…”
Section: Discussionmentioning
confidence: 55%
“…Imaging studies have been performed to explore normal brain processes involved in visceral perception, whether liminal or subliminal and its modulation by attention, conditioning and emotion [22,[28][29][30][31] . Several studies have also looked at the role of visceral perception in emotions and cognitive processes such as learning [32,33] .…”
Section: Ascending Spinal Pathwaysmentioning
confidence: 99%
“…Methods of brain imaging offer another investigative modality for addressing questions related to abnormal processing of sensory information in the cerebral cortex of IBS patients [84,[94][95][96] . Functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) are now commonly used to study information processing in the higher brain centers that underlie an individual's experience of conscious sensations.…”
Section: Sensory Processing In the Cerebral Cortexmentioning
confidence: 99%
“…Beyond the sensory cortices, fMRI and PET images show representation of both somatic and visceral sensation to be similar in the limbic and paralimbic regions of the cortex (e.g. anterior insular, anterior and posterior cingulate, prefrontal and orbitofrontal cortices [94,95] . These areas are known to be involved in the individual's motivational and emotional mood states and in the cognitive components of visceral sensations.…”
Section: Sensory Processing In the Cerebral Cortexmentioning
confidence: 99%